Student Publications’ Place in the Agricultural Communication Curricula - Kelsey Hall; Emily Rhoades; Robert Agunga (Journal of Applied Communications, 2009)
Many agricultural communication or journalism programs offer publication production opportunities as a way for students to use their writing, editing, design, and photography skills. This study evaluated the curriculum and make-up of student publications produced through these agricultural communication or journalism programs. The study also described the role advisers have in handling editorial, ethical, and legal issues. Data were collected through a questionnaire sent to members of the Academic Programs Special Interest Group in the Association for Communication Excellence. Fifteen programs identified offering a student-produced publication. The majority of these publications (n = 8) were offered as a course in an agricultural communication or journalism program, while five programs developed their publications as an extracurricular activity. Once the publication was produced, only three of the publications were reviewed and critiqued by industry professionals. While no advisers were concerned with obscenity issues, eight were concerned with a code of ethics, five were concerned with censorship, and four were concerned with libel issues. Recommendations are made for agricultural communication or journalism faculty.
Keywords: Publications; student; Curricula; Communication; Agriculture; recommendations; journalism; faculty.